PERANAN HUMAN RELATIONS TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR KELURAHAN JAWA SAMARINDA ULU - Lahai, Veronika Yanita (PREDIKSI, 2014)
The purpose of the research was to determine the extent to which the role of Labor Motivation towards Human Relations Officer At Administrative Office Java Samarinda ulu.Research done to employees in the Office is through two variabal, namely Human Relations with indicator Variables Relationship Formal, Non Formal Relations, and the provision of Guidance and direction. For variables. Employee motivation of working with indicators Giving Incentives a chance Followed education and Promotion. The author conducted research using the questionnaire and conduct hypothesis tests using the formula Price Relativ and get results that relationships between leadership and Employees walking pretty well.To further enhance Employee Job Motivation in addition to the factor of Human Relations, then other factors need to get attention so that existing Employees Work Motivation is increased will be maintained. With the Human Relations that exist within this Office expected working relationship can continue to improve the existing relationships.